Investigation of plasticizer production industry wastewater treatability using pressure-driven membrane process - Ozay, Yasin; Canli, Oltan; Unal, Bahar Ozbey; Keskinler, Bülent; Dizge, Nadir (Iwa Publishing, 2021)
In this study, the treatability of plasticizer production industry wastewater was investigated using nanofiltration (NF) and reverse osmosis (RO) membranes. The effect of operating pressure, pH of the wastewater, and sequential treatment option on the permeate flux, COD, phthalate, and micropollutant removal efficiencies were examined. The steady-state permeate fluxes of NF270, NF90, and BW30 membranes were 47.1, 19.0, and 13.9 L/m(2)/h for 15 bar, respectively. Sequential filtration using NF90 and BW30 membranes to protect the RO membrane was also tested. The initial and steady-state permeate fluxes were 30.4 and 18.9 L/m(2)/h, respectively, for 15 bar. The effect of wastewater pH in the range 4.0-10.0 was also studied and maximum initial and steady-state permeate fluxes were obtained at pH = 10.0. The permeate quality of NF90 and NF90 + BW30 membranes operated at 15 bar was measured and they showed a high degree for phthalate removal from wastewater from 97.7% to 99.9%. Moreover, a high degree of micropollutants was also obtained from 88.4% to 99.9% for sequential filtration (NF90 + BW30). The COD reduction efficiencies were obtained at 15 bar as 23.3%, 81.5%, and 87.6% for individual NF270, NF90, and BW30 membranes, respectively. However, COD reduction efficiency was increased up to 90.8% when sequential filtration (NF90 + BW30) was applied.
Keywords: membrane process; nanofiltration; phthalates; plasticizer production industry wastewater; reverse osmosis